Simulação numérica de fluxo de águas subterrâneas na bacia do Rio Grande (BA) - Gonçalves, Roger Dias [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The Urucuia Aquifer System represents a strategic water source in western Bahia. Its baseflow is responsible for the flow rate of the main tributaries of São Francisco river left bank in the dry season, including the Rio Grande, its main tributary in Bahia state. This river has a hydrological regime heavily affected by groundwater and is located in a region with conflicts about water resources. The aquifers geology is constituted by neocretacious sandstones of Urucuia Group subdivided in Posse Formation and Serra das Araras Formation. The embasement is formed by neoproterozoic rocks of Bambuí Group. This work focuses on an important tool application, the mathematical model, whose function is represent approximately and suitably the reality so that can assist in different scenarios simulations and make predictions. Many studies developed in this basin provided the conceptual model basis including a full free aquifer, lithological and hydraulical homogeneity in entire basin, null flux at plateau borders and aquifer base. The finite element method is the numerical method used and FEFLOW the computational algorithm. The simulated area was discretized in a single layer with 27.357,6 km² (314.432 elements and 320.452 nodes) totaling a 4.249,89 km³ volume. Were utilized 21 observation wells from CERB to calibrate the model. The terrain topography was obtained by SRTM data and the impermeable base was generated by interpolation of descriptive profiles from wells and electric vertical drilling from previous studies. Works in this area obtained mean recharge rates varying approximately from 20% to 25% of average precipitation, thus the values of model recharge zones varying in this range. Were distributed 4 hydraulic conductivity zones: (K1) west zone with K=6x10-5 m/s; (K2) center-east zone with K=3x10-4 m/s; (K3) far east zone with K=5x10-4 m/s; e (K4) east-north zone with K=1x10-5 m/s. Thereby was incorporated to the final conceptual model...

O Sistema Aquífero Urucuia representa um manancial estratégico no oeste baiano. Seu fluxo de base é responsável pela vazão dos principais afluentes da margem esquerda do rio São Francisco no período de estiagem, entre eles o rio Grande, seu principal afluente na Bahia. O rio Grande possui um regime hidrológico fortemente influenciado pela contribuição de água subterrânea e está localizado numa região com sérios conflitos pelo uso da água. A geologia do meio aquífero é constituída pelos arenitos neocretácicos do Grupo Urucuia, subdivididos em Formação Posse e Formação Serra das Araras, enquanto que o embasamento é composto por rochas neoproterozóicas do Grupo Bambuí. Este trabalho foca no uso de uma importante ferramenta no estudo de fluxo de águas subterrâneas, o modelo matemático, cuja função é a representação aproximada e adequada da realidade para que possa ser empregado na simulação de diversos cenários e fazer predições. Os vários estudos realizados na bacia proporcionaram a base para a elaboração de um modelo conceitual simplificado que inclui homogeneidade litológica e hidráulica em toda a bacia, fluxo nulo nos limites do platô e na base do aquífero, descarga de água subterrânea nas drenagens que cortam o aquífero e que este é livre em toda a sua extensão. O método numérico utilizado é o método dos elementos finitos empregado no algoritmo computacional FEFLOW. A área simulada foi discretizada em uma camada com 27.357,6 km² (314.432 elementos e 320.452 nós) perfazendo 4.249,89 km³ de volume e foram utilizados 21 poços de observação da CERB para fins de calibração. A topografia do terreno foi obtida através de dados SRTM e a base impermeável do modelo foi gerada a partir da interpolação de perfis descritivos de poços e SEVs de trabalhos anteriores. Trabalhos na área obtiveram taxas de recarga média variando aproximadamente de 20% a 25% da precipitação média, desse modo...
Keywords: Águas subterrâneas; Cursos de agua - Fluxo; Aquiferos; Hidrogeologia; Método dos elementos finitos; Grande, Rio, Bacia (BA)